STUDY OF BAUXITE RESIDUE EXTRACTION AS AN ALTERNATIVE RESOURCE IN THE UTILIZATION OF BAUXITE RESIDUE: A COMPREHENSIVE REVIEW - Giovanni Harjono, Geraldo
Aluminum is produced from bauxite ore by a combination of the Bayer process and the Hall-Heroult process. To produce one ton of aluminum, it generates 1 – 2.5 tons of red mud. Currently, the average generation of red mud is about 70 million tons per annum. The vast generation of red mud without a sustainable utilization process can promote an environmental problem. On the other hand, red mud consists of base metals and rare earth elements. Therefore, red mud is possible to be used as an alternative resource for metal production. This study covers the options of processing red mud, the comparison of metallurgical processing methods for the red mud, the effectiveness of each metallurgical process, and a possible zero-waste process for red mud by reviewing research papers published. The study began with collecting documents on the residue of bauxite, the processing of bauxite residue with pyrometallurgy, hydrometallurgy, and biohydrometallurgy. Next, each document was deeply reviewed to collect information based on the current objectives. Then, the results from reviewing papers were comprehensively discussed. The results of each discussion were summarized and a possible zero-waste process for red mud was proposed. Based on the literature study and the discussion, it concludes that red mud can be treated by pyrometallurgy, hydrometallurgical, and biohydrometallurgy. The pyrometallurgical process is focused on the retrieval of Fe and Al metals, whereas hydrometallurgical and biohydrometallurgical processes are used to extract rare earth element and heavy metals. Pyrometallurgy for red mud is usually operated at a temperature of 1200-1400 °C and with the addition of Na2CO3 CaCO3, or MgCO3 and CaO. The hydrometallurgical process for red mud requires a strong acid, such as HNO3 at elevated temperature. Meanwhile, the biohydrometallurgical process for red mud shows a possible extraction process at room temperature by Penicillium tricolor with a pulp density of 2% w/v. By combining the possible processes and the applications of its products, red mud can be treated as metal resources, component for construction materials, and fertilizer product, thus resulting no waste product.